Physical activity counseling in maternity and child health care - a controlled trial - Kinnunen Tarja I; Fogelholm Mikael; Pasanen Matti; Aittasalo Minna; Ojala Katriina; Luoto Riitta (BMC, 2008)
Abstract Background The purpose of the study is to examine the effects and feasibility of individual physical activity (PA) counseling in maternity and child health clinics in Finland. Methods Three clinics including both maternity and child health care signed up for the experimental (EXP) and three for the control group (CON). The participants were 132 pregnant and 92 postpartum primiparas. The nurses in EXP integrated a primary and four booster PA counseling sessions into routine visits. An option for supervised group exercise was offered. In CON former practices, usually including brief PA advice, were continued. Leisure-time PA (LTPA) prior to pregnancy was elicited by questionnaire and followed 16-18 and 36-37 weeks' gestation in maternity clinics and 5 and 10 months postpartum in child health clinics. Feasibility included safety, participant responsiveness, realization of counseling and applicability. Results According to analysis of covariance adjusted for baseline LTPA and possible confounders, no relative between-group differences in LTPA were found at the first follow-up in either maternity or child health clinics. At the last follow-up in maternity clinics the weekly number of at least moderate-intensity LTPA days was 43% (95% CI: 9, 87) higher and the weekly duration of at least moderate-intensity LTPA 154% (95% CI: 16, 455) higher in EXP compared with CON. Counseling proved feasible in both maternity and child health clinics. Conclusion Counseling encouraged pregnant women to sustain their moderate-intensity LTPA and was feasible in routine practices. No effects were observed if counseling was initiated postpartum. Trial registration Current Controlled Trials ISRCTN21512277